Belonging and collaboration in clinical education - Courtney Lewis; Alivia English (International Journal for Students as Partners, 2026)
Effective clinical education depends on strong student–educator partnerships, yet the processes that support or hinder these relationships remain poorly understood. This study examined perspectives of clinical educators (CEs) and students on fostering belonging in clinical education. Members of the Student-Instructor Partnerships in Clinical Education (SIPCE) learning community, representing diverse health professions, participated in focus groups. Discussions explored definitions of belonging, barriers to partnership, and strategies for strengthening relationships. Thematic analysis revealed key facilitators, including recognition of both students and CEs as whole people, active engagement, and timely, constructive feedback. Barriers included power imbalances, role ambiguity, and students’ fear of failure. Mutual respect, empathy, and intentional collaboration were identified as essential for effective partnerships. Positive relationships enhanced confidence, engagement, and willingness to take learning risks, while barriers constrained outcomes. Findings highlight the importance of addressing power dynamics and fostering trust to optimize clinical learning environments.